BIBLIOMETRIC ANALYSIS OF SCIENTIFIC PRODUCTION IN REVISTA DE ADMINISTRAÇÃO DA UFSM: IN SEARCH OF NEW PERSPECTIVES AND CHALLENGES - Jordana Marques Kneipp (Revista de Administração da UFSM, 2013)
The Revista de Administração da Universidade Federal de Santa Maria (ReA/UFSM), founded in 2008, is an online publication of the Departamento de Ciências Administrativas of Centro de Ciências Sociais e Humanas from UFSM. The ReA/UFSM is gaining its place in academiaas an important vehicle for dissemination of publications in the business area. In this sense, this study aimed at analyzing the scientific publications of ReA/UFSM, in the period from 2008 to 2011. Thus, we analyzed all papers published in the periodic, in the last four years, representing 113 studies. Among the main results, it was found that the papers analyzed are mostly empirical, exploratory in nature, with qualitative approach predominantly. The analyzed data allow present an overview of the publications of ReA/UFSM, in the period from 2008 to 2011, enabling to defined new perspectives and challenges for the periodic.